Role of Isolates of Bacillus Species for Biodegradation of Multiple Contaminants - Sarwan, Jyoti; Bose K, Jagadeesh Chandra (Journal of Sustainability and Environmental Management, 2022)
Nature is the precious gift for every organism on the earth but, only few species are taking benefits and rest are suffering from scarcity of natural resources because of over exploitation. There exist numbers of hazardous pollutants in environment that are required to eradicate for sustainable use of natural resources. To overcome these pollutants researchers introduced bioremediation with microorganisms. This paper has been prepared by collecting data from various research articles to show numerous applications of bacillus species for sustaining environment. The article is unique from other research studies as it elaborates removal of different pollution causing elements such heavy metals, soil contaminants, removal of dye contaminants from the environment. Although there are large numbers of microbial species to degrade pollutants but according to recent researches, Bacillus is more prominent among all bacterial species. Researchers have proved that Bacillus are safer and cheaper source for conserving environment and reduce toxics from environment. Removal of heavy metals such as cadmium, nickel, copper can be done with the help of Bacillus cereus. In waste water treatment, Bacillus licheniformis and Bacillus acidophilus are also responsible for reducing nitrogenous components like phosphates, nitrites and ammonia.